Global strategic management - Peng, Mike W. (South Western, 2009)
Introduce a broadened definition of "global strategy"; comprehensive and innovative coverage; in-depth and consistent explanations of cutting-edge research; and an interesting and accessible way to engage students. The text uses the "strategy tripod"--analyzing strategy from the industry-, institution-, and resource-based views--to answer the question: What determines the success or failure of firms around the globe?